2005
DOI: 10.1039/b507201h
|View full text |Cite
|
Sign up to set email alerts
|

The structural and magnetization studies of Co-doped ZnO co-doped with Cu: Synthesized by co-precipitation method

Abstract: Co-and Cu-doped ZnO of nominal composition Zn 0.95 Co 0.05 O and Zn 0.94 Co 0.05 Cu 0.01 O were synthesized by a co-precipitation method in organic media. Rietveld refinement of X-ray diffraction data of the samples annealed at 725 K showed that they are single phase without any secondary phases. DC magnetization measurements of samples with Cu co-doping (Zn 0.94 Co 0.05 Cu 0.01 O) as a function of field at room temperature showed a ferromagnetic signature while the samples without Cu co-doping (Zn 0.95 Co 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 26 publications
5
31
0
Order By: Relevance
“…This supports well the experimental findings that additional Cu doping can achieve roomtemperature ferromagnetism in paramagnetic Co-doped ZnO. 23,25,26 In the Zn 13 Co 2 Cu 1 O 16 system the most stable configuration is the "fully scattered" configuration 5 with a FM coupling because of its lowest total energy. Its E f is lower by 23 meV/Co than that of the "compact" configuration 2 with a FM coupling, having the second lowest total energy.…”
supporting
confidence: 77%
“…This supports well the experimental findings that additional Cu doping can achieve roomtemperature ferromagnetism in paramagnetic Co-doped ZnO. 23,25,26 In the Zn 13 Co 2 Cu 1 O 16 system the most stable configuration is the "fully scattered" configuration 5 with a FM coupling because of its lowest total energy. Its E f is lower by 23 meV/Co than that of the "compact" configuration 2 with a FM coupling, having the second lowest total energy.…”
supporting
confidence: 77%
“…It is observed that the intensity of magnetization varies linearly with the applied magnetic field for all the prepared compounds which reveals the paramagnetic nature of the resultant compounds [11,12]. In the earlier reports, it is identified that the parent compound Nd 2 CuO 4 exhibits paramagnetic nature [13] and the same is obtained for both parent and prepared compounds now.…”
Section: Magnetization Analysissupporting
confidence: 49%
“…[2][3][4][5][6][7][8][9][10] For practical spintronic applications DMS with Curie temperature, Tc, above RT are required. Many promising oxides like TiO 2 , ZnO and SnO 2 and III-V semiconductor GaN doped with transition metal ions have been reported to exhibit ferromagnetic behavior near or above room temperature, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] but the origin of ferromagnetism in these systems is poorly understood. Oxide systems based on host semiconductor with high solubility of magnetic ions are highly desirable to form thermodynamically stable magnetic semiconductors.…”
mentioning
confidence: 99%